Nutrition Training for Madrasah Ibtidaiyah Teachers in Semarang Regency - Widajanti, Laksmi; Qothrunnada, Alisa; Hidayah, Aisyah Nurul (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The purpose of this study was to analyze the knowledge of Madrasah Ibtidaiyah (MI) teachers in Semarang Regency about nutrition. This study used a quasi-experimental design. Seventeen teachers were provided with training covering four modules in four hours. The data obtained were analyzed using ANOVA. It showed that the understanding of 94% of the teachers about nutrition had a score higher than 60. There was a slight increase in the knowledge of nutrition among the teachers but it was not statistically significant (F=2.395; p=0.173). It is concluded that training on nutrition for MI teachers in Semarang Regency slightly increased their knowledge on nutrition.